A novel high-efficiency stable atmospheric microwave plasma device for fluid processing based on ridged waveguide. (29th August 2017) - Xiao, Wei; Huang, Kama; He, Jianbo; Wu, Ying
Abstract: The waveguide-based microwave plasma device is widely used to generate atmospheric plasma for some industrial applications. Nevertheless, the traditional tapered waveguide device has limited power efficiency and produces unstable plasma. A novel ridged waveguide with an oblique hole is proposed to produce microwave atmospheric plasma for fluid processing. By using the ridged waveguide, the microwave field can be well focused, which can sustain plasma at relatively low power. Besides, an oblique hole is used to decrease the power reflection and generate a stable plasma torch especially in the case of high flowing rates. Experiments have been performed with the air flowing rates ranging from 500 l h −1 to 1000 l h −1 and the microwave working frequency of 2.45 GHz. The results show that in comparison with the conventional tapered waveguide, this novel device can both sustain plasma at relative low power and increase the power transfer efficiency by 11% from microwave to plasma. Moreover, both devices are used to process the waste gas-CO and CH4 . Significantly, the removal efficiency for CO and CH4 can be increased by 19.7% and 32% respectively in the ridged waveguide compared with the tapered waveguide. It demonstrates that the proposed device possesses a great potential in industrial applications because of its high efficiency and stable performance.